MODEL LAYANAN INFORMASI LOKASI MASJID DI WILAYAH KOTA TANGERANG MENGGUNAKAN PERANGKAT BERGERAK (MOBILE DEVICE) - Angga Aditya Permana (Jurnal Teknik, 2016)
MuslimisthebiggestinhabitantinIndonesia,sothatthey needanextraordinary servicewhich canprovide informationabouttheirobligatory religiousactivity inthis caseissholat.Sholat is preferabledoneatmosqueespeciallyformale.Therefore, informationaboutthenearestmosque ismuchneeded,especiallyformobileusereven traveler. Thisinformationisimplicatedinmobile device,thereforeusercanaccess wheneverandwhereverasquickaspossible.Servicethatwillbe modeledinthis research exploiting Global Positioning System(GPS)on android mobile devices based on  LocationBased  Service  (LBS).This  servicemodel  is  developedfor  providing information about location and historical background of mosquein Tangerang.Keywords:  Android,  Global  Positioning  System,  Location Based  Service,  MobileDevice.